Study of surface morphology and grain size of irradiated MgO thin films - Singh, J.P.; Sulania, I.; Prakash, J.; Gautam, S.; Chae, K.H.; Kanjilal, D.; Asokan, K. (VBRI Press, 2012)
Present work reports 200 MeV Ag15+ irradiation induced effects on the surface morphology, grain size and local electronic structure in MgO thin films deposited by e-beam evaporation under ultra High vacuum. The grain size was found to decrease from 37 nm (pristine film) to 23 nm for the sample irradiated with fluence of 1×1012 ions/cm2 and thereafter it increases upto fluence of 5×1012 ions/cm2. Similar changes with ion fluence were also observed for surface roughness. Shifting and disappearance of peaks in X-ray absorption spectra with irradiation shows the electronic structure modification after irradiation. The detailed analysis of observed results has been done on the basis of existing theories. ？ 2012 VBRI Press.